A multiphase approach for evaluating the horizontal and rocking impedances of pile group foundations - Nguyen, V.T.; Hassen, G.; de Buhan, P. (International journal for numerical and analytical methods in geomechanics, 2016)
Summary This paper advocates the use of a multiphase model, already developed for static or quasi‐static geotechnical engineering problems, for simulating the behaviour of piled raft foundations subject to horizontal as well as rocking dynamic solicitations. It is shown that such a model, implemented in a FEM code, yields appropriate predictions for the foundation impedance characteristics, provided that shear and bending effects in the piles are taken into account, thus corroborating the findings of the asymptotic homogenization theory. Besides, it is notably pointed out that such a multiphase‐based computational tool makes it possible to assess the dynamic behaviour of pile groups in a much quicker way than when using direct numerical simulations, which may face oversized problems when large pile groups are concerned. Copyright © 2016 John Wiley & Sons, Ltd.